2016
DOI: 10.1080/15384101.2016.1183851
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated ERK1/2 MAP kinase signaling promotes aneuploidy by a Fbxw7β-Aurora A pathway

Abstract: Aneuploidy is a common feature of human solid tumors and is often associated with poor prognosis. There is growing evidence that oncogenic signaling pathways, which are universally dysregulated in cancer, contribute to the promotion of aneuploidy. However, the mechanisms connecting signaling pathways to the execution of mitosis and cytokinesis are not well understood. Here, we show that hyperactivation of the ERK1/2 MAP kinase pathway in epithelial cells impairs cytokinesis, leading to polyploidization and ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…oxidative stress [ 38 ]. Also a hyperactivation of ERK1/2 is reported to promote aneuploidy by polyploidization [ 39 ]. However, the mechanisms how the absence of the eEF2 kinase impairs this pathway remain unclear and have to be subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…oxidative stress [ 38 ]. Also a hyperactivation of ERK1/2 is reported to promote aneuploidy by polyploidization [ 39 ]. However, the mechanisms how the absence of the eEF2 kinase impairs this pathway remain unclear and have to be subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive activation of the oncogenic ERK1/2 MAP kinase (MAPK) pathway results in the downregulation of FBXW7β both in epithelial cell lines and in the intestine tissue of a transgenic mouse model, conferring the stabilization of Aurora-A, abnormal cell division, and polyploidization. Consequently, the ERK1/2/FBXW7/Aurora-A axis is associated with aneuploidy and epithelial malignancies, and the MAPK can be a good candidate for target therapy in the not-too-distant future ( 170 ). Under the governance of p53-dependent transcription regulation, FBXW7 protects epithelial cells from DNA damage and malignant progression presumably through its substrate such as cyclin E, Aurora A, or c-MYC, and p53 heterozygosity combined with FBXW7 loss can confer aneuploidy as well as epithelial cancers ( 171 ).…”
Section: Fbxw7 and The Hallmarks Of Cancermentioning
confidence: 99%
“…Based on an in vitro TR CRC cell model, we demonstrated that Fbxw7 was significantly downregulated in HCT-116 TR cells, suggesting that enhancing the Fbxw7 signaling pathway could contribute to overcoming Taxol resistance. Fbxw7 functions as a tumor suppressor and is negatively associated with tumor progression through targeting a cluster of oncoproteins, such as c-Myc (16), cyclin E (16), mTOR (17), and Aurora A (18). Despite the fact that diverse Fbxw7 substrates have been validated, novel oncoproteins of potential Fbxw7 targets and the molecular mechanisms underlying the functions of Fbxw7 in chemosensitivity remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%